How to Measure the State of Flow in Learning? Testing of the Study-Related Flow Inventory on a Sample of Russian Students - Alina E. Ivanova; Ilya S. Denisov (Voprosy obrazovaniya / Educational Studies Moscow, 2024)
The state of "flow" is experienced by a person who is so immersed in an activity that he or she is not paying attention to anything around them.  Flow state can play an important role in educational achievement. Researchers around the world have shown that a flow state is positively related to self-esteem, life satisfaction, psychological well-being, and, to some extent, educational achievement in students. There are currently no questionnaires in Russian that can measure the flow state in learning quickly and reliably enough. This paper will describe the process of localizing the study-related flow inventory in Russian and present the initial results of its validation. Validation was conducted on a sample of about 600 individuals who, at the time of the survey, were in the process of learning. Confirmatory factor analysis was used to gather evidence of construct validity; the functioning of the scale for different groups of survey participants was also investigated; in addition, the item response theory was applied to assess the reliability of the scale, to assess the quality of individual scale items, and to investigate the functioning of individual categories. Like the original version, the Russian-language scale is quite reliable and also demonstrates invariance to the conditions of heterogeneous samples of subjects: by gender, by work/study status, and by the way the sample was obtained. The application of the scale in the Russian context highlighted the problem with the scale structure, which was previously shown by researchers from some countries when trying to adapt the scale into the languages of their countries. Overall, the Russian-language version of the study-related flow inventory can be successfully applied in Russian research practice.